2017 Infectious Diseases Society of America Physician Compensation Survey: Results and Analysis. (22nd November 2018) - Trotman, Robin; Kim, Alice I; MacIntyre, Ann T; Ritter, Jethro Trees; Malani, Anurag N
Abstract: Analyzing health care reimbursement is a dynamic process. Infectious Diseases (ID) physicians have careers in diverse practice models. With current compensation models focusing on value and quality metrics, ID physicians are poised to be at the forefront of these delivery models. Monitoring and disseminating the current status of ID physician compensation are priorities of the Infectious Diseases Society (IDSA). In 2015, the IDSA conducted the largest ID physician compensation survey to date. The data were analyzed and disseminated, and the society subsequently responded with a plan to continue to develop and collect the most comprehensive and accurate data on ID physician compensation. Therefore, from May to June 2017, the IDSA conducted a follow-up compensation survey of its members. This survey resulted in the largest number of respondents of any ID compensation survey. It revealed that compensation across the different practice demographics had increased since the 2015 survey and is generally higher than salaries published in other comparable surveys. These data and the subsequent analyses focus on physicians who report patient care as their primary responsibility; they are presented by members of the IDSA's Clinical Affairs Committee.